The Emotive Function of Addressing. An Empirical Analysis Based on German-Italian Political Facebook Comments - Ponzi, Maria Francesca (ANNALI. SEZIONE GERMANICA. Rivista del Dipartimento di Studi Letterari, Linguistici e Comparati dell’Università degli studi di Napoli L’Orientale, 2021)
This study aims to investigate the emotive function of forms of address. Despite the customary propensity of the (linguistic) sciences to marginalise the problematic issue of emotional expression, emotionality still plays a fundamental role in understanding the correct use of forms of address. Indeed, terms of address are capable not only of expressing the power dynamic that obtains between interlocutors, they are also a mark of the speakers’ respective psychological attitudes. As far as methodology is concerned, the emotive function of forms of address will be analysed by considering a corpus of Facebook comments addressed to German and Italian politicians. The analysis pays closer attention to the correlation between the emotive value of the forms of address and the female identity of the addressees and its relevant communicative consequences. This work focuses, finally, on the specific use of the forms of address in German and in Italian. This contrastive aspect highlights not only linguistic but also cultural features.